(untitled) (World Bulletin of Public Health, 2023)
Osteointegration of implants continues to generate scientific and practical interest. Currently, implant systems have great potential, which contributes to the engraftment of implants and their acceptance by bone tissue in 95% of cases [1,15]. Implantation is considered as the most effective method of treating jaw defects, directly related to the quality of life of patients